Exploring the Role of the Amplitude Envelope in Duration Estimation. (July 2014) - Vallet, Guillaume T; Shore, David I; Schutz, Michael
A sound's duration provides important information about the event producing it. Although many of the sounds we hear every day are 'percussive' in nature (ie resulting from two objects impacting) and therefore exhibit decaying/damped amplitude envelopes, perceptual experiments frequently use tones synthesized with 'flat' or abruptly ending envelopes. Such sounds afford an estimation strategy involving calculating the elapsed time between tone onset and offset—a strategy that would be problematic for ecologically pervasive decaying sounds. Here we compare duration judgments for tones with percussive (ie gradually decaying) and flat (ie abruptly ending) amplitude envelopes, finding evidence for the use of different strategies. This result is discussed in terms of its implications for dominant theories and models of sensory perception that are often assessed using artificial sounds (ie 'flat tones') affording strategies that may not be optimal or even available for everyday listening.